2008
DOI: 10.1016/j.addbeh.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated days of smoking cue exposure on urge to smoke and physiological reactivity

Abstract: The present study investigated the effects of repeated days of laboratory-based smoking cue exposure on subjective and physiologic cue reactivity. Twenty non-treatment seeking moderate/heavy smokers completed three laboratory sessions approximately 7 days apart, each following a 10-hour nicotine deprivation period. Cue reactivity procedures consisted of a relaxation trial followed by two trials of in vivo cue exposure. Dependent measures included urge to smoke, a withdrawal questionnaire, mean arterial pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…To our best knowledge, this is the first study to compare cue-induced craving and physiological reactions between recently and long-abstinent heroin-dependent individuals. Our findings were consistent with several related studies in smokers, which found that elevated craving and higher physiological reactions can be reliably elicited over repeated cue reactivity sessions (LaRowe, Saladin, Carpenter, & Upadhyaya, 2007; Miranda, Rohsenow, Monti, Tidey, & Ray, 2008). Furthermore, one study found cue-induced craving increases with duration of abstinence in smokers (Bedi G, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…To our best knowledge, this is the first study to compare cue-induced craving and physiological reactions between recently and long-abstinent heroin-dependent individuals. Our findings were consistent with several related studies in smokers, which found that elevated craving and higher physiological reactions can be reliably elicited over repeated cue reactivity sessions (LaRowe, Saladin, Carpenter, & Upadhyaya, 2007; Miranda, Rohsenow, Monti, Tidey, & Ray, 2008). Furthermore, one study found cue-induced craving increases with duration of abstinence in smokers (Bedi G, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…However, participants were not permitted to light the cigarette and were asked to instead imagine that the cigarette had been lit. Although many studies involving in vivo cue exposure to cigarettes require participants to actually light the cigarette (e.g., Havermans et al 2003;Miranda et al 2008), the methodology for the present study was altered to avoid cue reactivity complications that may arise due to the release of nicotine from cigarette smoke. Specifically, we thought that the release of nicotine from a lit cigarette might result in less craving than an unlit cigarette that does not allow for the release of nicotine.…”
Section: Methodsmentioning
confidence: 99%
“…In one of the most widely used paradigms, smokers are given access to their own brand of cigarettes and directed to handle and light a cigarette without smoking it (Sayette, Martin, Wertz, Shiffman, & Perrott, 2001). This experimental paradigm has been shown to reliably evoke cue-induced cravings (Carter & Tiffany, 1999;Miranda, Rohsenow, Monti, Tidey, & Ray, 2008;Sayette & Parrott, 1999;Sayette et al, 2001). However, the observed absolute level of craving can sometimes be modest ) and can be influenced by whether a subject expects to smoke following exposure (Dols, van den, Kindt, & Willems, 2002;Sayette et al, 2003;Wilson, Sayette, Delgado, & Fiez, 2005).…”
Section: Cue Exposure Studiesmentioning
confidence: 97%